Cultural and Behavioral Factors Related with Non-compliance to Hygienic Rules by Food Vendors in Primary and Secondary School in the Benoue Division - Cameroon - Dama, Ulrich; Socpa, Antoine; Nsoh, Marius (Jour Med Resh and Health Sci, 2021)
Background: Unhealthy foods containing harmful bacteria, viruses, parasites, or chemicals cause illnesses ranging from diarrhea to cancer. The objective of this study was to investigate the behavioral and cultural practices responsible for non-compliance with hygiene rules by commercial food vendors in primary and secondary schools in the Benoue division of Cameroon. Based on the results obtained, we recommend to decision-makers the need to ensure a quality diet served in schools, respect for hygiene rules and the practice of regular physical activity which both contribute to the good - cognitive and mental being of children. Method: We conducted a descriptive cross-sectional analysis in the Benoue division of Cameroon. Quantitative and qualitative methods were used for data collection. Prospective data were collected from 172 food vendors within this locality. A well-structured questionnaire and an observation guide were used for data collection. Ethical approval was provided by the IRB of the Catholic University of Central Africa. Results: The results show that 57% of participants were not aware of neither practiced optimal hygiene rules. More than 78.1% of the respondents did not wash their hands before serving food. Other cultural and behavioral determinants such as cleanliness, wearing of aprons, and owning a dust bin influenced vendors' respect of hygienic rules with a significance of 05% (p <0.05). Conclusion: Our findings show that cultural and behavioral determinants factors influence the practice of hygienic rules in schools. Training these minor business owners on adequate hygienic practice will optimize respect for aseptic rules.